THE NEEDS FOR DEVELOPING TEACHERS OF BANGKOK OFFICE OF LEARNING ENCOURAGEMENT BASED ON THE CONCEPT OF MEANINGFUL WORK - Pinpreechachai, Kamonchanok; Kulophas, Dhirapat (Journal of Educational Review Faculty of Education in MCU, 2024)
This research aimed to investigate the requirements for the developing teachers of Bangkok Office of Learning Encouragement, based on the concept of meaningful work. The research methodology used in this study was descriptive research. The research was completed by 180 people, who were teachers under at Bangkok Office of Learning Encouragement. The tools used in the research were questionnaires on the current state and desired state of developing teachers of Bangkok Office of Learning Encouragement based on the concept of meaningful work. The data analyzed by arithmetic mean, standard deviation, and the modified Priority Needs Index (PNIModified). The research findings indicate the following requirements for developing teachers of Bangkok Office of Learning Encouragement, based on the concept of meaningful work: The highest level of necessity is related to appreciation and meaning in working (PNIModified = 0.493), happiness in working (PNIModified = 0.484), positive motivation in working (PNIModified = 0.441) and great values in working (PNIModified = 0.437) are also considered necessary.